Tissue engineering and regenerative medicine research - how can it contribute to fight future pandemics? - Caballero, David (2020)
Understanding the pathogenesis of viral infection is of paramount importance for the development of better therapies. In the particular case of COVID-19, the mechanism of infection is highly complex and involves a critical cascade of events, which can lead to the death of the patient. Intense research is currently being performed to gain mechanistic insights about the virus etiology and to evaluate new therapeutic approaches. The development of point-of-care diagnostic tools, predictive drug screening platforms, and biomimetic models of the disease could play a key role in understanding the cellular and molecular mechanism of viral infection and its response to drugs. In this regard, specific tissue engineering and regenerative medicine approaches, such as microfluidics and organ-on-a-chip technologies, as well as bioprinted in vitro disease models, could be used to develop a technological platform to fight COVID-19, and other virus pandemics yet to come. Herein, we briefly discuss about how such approaches can contribute to address current and future viral pandemics by highlighting recent successful examples.